2007
DOI: 10.4161/cbt.6.10.4742
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase I in human carcinomas: A novel role in histone deacetylation?

Abstract: KEy wordScarnitine palmitoyltransferase I (CPT1), fatty acid synthase (FAS), histone deacetylase activity, cancer, immunohistochemistry, metabolism, histone deacetylase inhibitors. ABBrEviAtionS ABStrACtCarnitine palmitoyl transferase I (CPT1) catalyzes the transport of long-chain fatty acids into mitochondria for b-oxidation. A link between CPT1 and apoptosis has been suggested on the basis of several experimental data. Nevertheless, results are contradictory about the effective role of CPT1 in cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
0
45
1
Order By: Relevance
“…Mazzarelli et al (2007) recently observed that the CPT I was significantly decreased in the mitochondria, and it strikingly localized in the nuclei of tumoral tissues (colon, breast, liver, ovary). At this purpose, in vitro experiments using epithelial neoplastic (MCF-7, Caco-2, HepG2) cells and nonneoplastic cell lines (MCF-12F) confirmed a nuclear localization of CPT1 protein exclusively in neoplastic cells.…”
Section: Shifting Of Clu Forms During Tumor Progressionmentioning
confidence: 96%
“…Mazzarelli et al (2007) recently observed that the CPT I was significantly decreased in the mitochondria, and it strikingly localized in the nuclei of tumoral tissues (colon, breast, liver, ovary). At this purpose, in vitro experiments using epithelial neoplastic (MCF-7, Caco-2, HepG2) cells and nonneoplastic cell lines (MCF-12F) confirmed a nuclear localization of CPT1 protein exclusively in neoplastic cells.…”
Section: Shifting Of Clu Forms During Tumor Progressionmentioning
confidence: 96%
“…The liver isoform, CPT1A, is overexpressed mainly in cancers affecting blood cells, such as chronic myeloid leukemia and acute myeloid leukemia [121]. It has been proposed that CPT1A contributes to cell survival, not only by increasing FAO [122] but also stimulating histone acetylase activity in the nucleus [123]. Interestingly, Cpt1c has also emerged as a key gene in tumor cell survival in certain types of cancer [124].…”
Section: Cpt1c In Tumor Cellsmentioning
confidence: 99%
“…CML, chronic myelogenous leukemia; AML, acute myelogenous leukemia; ALL, acute lymphoblastic leukemia. for fulfilling their metabolic needs, particularly when more broadly expressed family members, namely CPT1A and CPT1B, are also available but apparently not activated in cancer cells (44). Presumably, both CPT1A and CPT1B can also increase FAO (45,46), so it stands to reason that CPT1C upregulation must provide a special activity that spurs tumor growth.…”
Section: Why Cpt1c?mentioning
confidence: 99%